Strategi Marketing Public Relations dalam Meningkatkan Image PT. BPRS Sarana Prima Mandiri Pamekasan - Itawah; Nuryana, Fatati (Mabny: Journal of Sharia Management and Business, 2022)
The development of the banking world in Indonesia is so rapid, causing increasingly fierce market competition between banks, both conventional banking and Islamic banking. There are two focus of research in this study, namely how the marketing public relations strategy in improving the image of PT. BPRS Sarana Prima Pamekasan and what are the opportunities and obstacles of marketing public relations in improving the image of PT. BPRS Sarana Prima Mandiri Pamekasan. This study uses a qualitative approach, the source of the data obtained through interviews, observation and documentation. The technique of checking the validity of the data is through the extension of participation, the persistence of researchers, and triangulation. The results of the research that the marketing public relations strategy in improving the image of PT. BPRS Sarana Prima Mandiri Pamekasan in addition to the use of attributes and services with good quality, also the distribution of free basic necessities can have a positive influence on the company's image. And regarding the opportunities and obstacles to marketing public relations in improving the image of PT. BPRS Sarana Prima Pamekasan, namely about the opportunity itself, namely the increasing number of customers in carrying out a storage, financing, and transaction and regarding the obstacles to the existence of banks around the SPM can provide barriers to SPM itself.